Urban void as an urban catalyst bridging the gap between the community - Aleha, Anum; Zahra, Syeda Mahwish; Qureshi, Sabeen; Marri, Sohrab Ahmed; Siddique, Sarah; Hussain, Samar Shamim (Frontiers in Built Environment, 2023)
Due to the increase in population, there are fewer open spaces creating urban voids in cities nowadays. However, the opportunities made available to people by urban voids adequately indicate the necessity and significance of urban open spaces. The lack of proper planning and a good perception of the place led to the formation of lost spaces. These lost spaces are found everywhere and are treated as waste spaces. By reclaiming these urban voids, we can change them into public gathering spaces, pocket parks, or any user-friendly space admired by the users. The objective of the study is to determine why these waste spaces are called urban voids and are not utilized to their full potential. The identified area for the case study is near Railway Colony in Multan. The selected area is L-shaped and connected with the base of a flyover, which creates a huge void. The spatial methodology, which is based on identifying the physical conditions and surveys, which depend on user ratings, was the foundation of the research methodology. Users assigned ratings for the space performance, which was determined by the spatial analysis approach and differed in terms of space structure and attributes. A total of 280 participants (118 females and 162 men) rated the technical, functional, and aesthetic performance of the spaces they occupy using a Likert attitude scale, with 70 individuals from each of the identified connected urban voids under the flyover. The results showed that space performance affects user satisfaction and the space usage level after design interventions.